Added prognostic value of secondary AML-like gene mutations in ELN intermediate-risk older AML: ALFA-1200 study results - Gardin, Claude; Pautas, Cécile; Fournier, Elise; Itzykson, Raphaël; Lemasle, Emilie; Bourhis, Jean-Henri; Adès, Lionel; Marolleau, Jean-Pierre; Malfuson, Jean-Valère; Gastaud, Lauris; Raffoux, Emmanuel; Lambert, Juliette; et al. (Blood advances, 2020)
In this study, we aimed to refine prognostication of older with acute myeloid leukemia (AML) after intensive chemotherapy. Five hundred and nine patients aged 60 years or older (median age, 68 years) were prospectively enrolled in the intensive Acute Leukemia French Association (ALFA)-1200 trial between 2012 and 2016, and 471 patient samples were submitted to multigene analysis. Mutations in any of 8 genes frequently altered in myelodysplastic syndromes (MDS), including ASXL1, SRSF2, STAG2, BCOR, U2AF1, EZH2, SF3B1, and ZRSR2, defined a secondary AML (sAML)-like disease, as reported. Of the samples analyzed, 48% included sAML-like gene mutations. These mutations were associated with a shorter event-free survival, both overall (hazard ratio, 1.46; 95% confidence interval, 1.19-1.79; P < .001) and within the European LeukemiaNet (ELN)-2017 intermediate-risk subgroup (hazard ratio, 1.52; 95% confidence interval, 1.01-2.28; P = .044), which excludes ASXL1-mutated cases by definition. We therefore included patients with intermediate-risk AML carrying sAML-like mutations in a single high-risk patients group together with adverse-risk patients with AML, whereas other intermediate-risk patients were included in a standard-risk group together with favorable-risk patients (high-risk/standard-risk patient ratio, 1.00). Using this 2-class risk assessment, we observed that transplantation prolonged overall survival from remission in patients with high-risk AML only, not in patients with standard-risk AML. Routine analysis of sAML-like gene mutations may thus improve the definition of high-risk older patients with AML, and better identify the half of older patients who clearly derive survival benefit from allogeneic transplantation in first remission. This trial was registered at www.clinicaltrials.gov as #NCT01966497. •Secondary AML-like gene mutations other than ASXL1 also identify a substantial subset of patients with intermediate-risk AML and a worse outcome.•In one-third of AML of the ELN 2017 intermediate-risk group, sAML-like mutations other than ASXL1 can be detected. [Display omitted]